Fractionation and Hydrolyzation of Avocado Peel Extract: Improvement of Antibacterial Activity - Igor Trujillo-Mayol; Nidia Casas-Forero; Edgar Pastene-Navarrete; Fabiana Lima Silva; Julio Alarcón-Enos (MDPI AG, 2020)
Avocado Hass (Persea americana Mill) peel extract (APE) has the potential as a natural ingredient to substitute for chemical preservatives. The objectives of this study were to assess the phytochemical composition by high-performance liquid chromatography-quadrupole time-of-flight mass/mass spectrometry (HPLC-qTOF-MS/MS), total phenolic content (TPC), proanthocyanidin (PAC) content, and antioxidant activity of the APE, the organic fraction (OF), the aqueous fraction (AF), and the acid-microwave hydrolyzed APE (HAPE), on the antibacterial activity (ABA). The results indicated that APE and OF contained (p ˂ 0.05) a higher phenolic composition and antioxidant activity than AF and HAPE. The ABA specified that Pseudomonas aeruginosa and Bacillus cereus were inhibited by all the extracts (minimal inhibitory concentration-MIC ≥ 500 µg/mL), Staphylococcus aureus was only significantly inhibited by APE (≥750 µg/mL), the same MIC was observed for the OF on Salmonella spp. and Listeria monocytogenes. The HAPE increased the inhibitory efficiency up to 25% on Escherichia coli and Salmonella spp. (MIC ≥ 750 µg/mL), and 83.34% on L. monocytogenes (MIC ≥ 125 µg/mL) compared to APE (MIC ≥ 750 µg/mL). Also, HAPE inhibited the biofilm formation at the lowest concentration (125 µg/mL); meanwhile, the biofilm disruption showed to be concentration-time-dependent (p ˃ 0.05) compared to amoxicillin. In conclusion, the fractionation and hydrolyzation of APE improved the ABA; thus, those strategies are useful to design new antimicrobial compounds.